Dental maturation in a Chinese sample using Demirjian method - Yue Fei; Lianyi Yang; Kai Sheng; Guangyun Lai; Jun Wang (Taylor & Francis Group, 2021)
Background Dental calcification information is relevant for clinical, archaeological, and forensic applications. However, dental maturity measurements in current cohorts of Chinese children are insufficient. Aim This study aimed to establish the mandibular dental maturity table and determine the accuracy of dental age estimation using the Demirjian method in a Chinese sample. Subjects and methods Permanent mandibular teeth, excluding the third molar, in 2091 panoramic radiographs of 1008 males and 1083 females aged 3-15 were graded, and dental age was estimated according to Demirjian's criteria. Age-of-attainment was calculated with probit regression for each stage by sex, and sex differences were analysed using the Mann-Whitney U test. Dental age was compared with chronological age using paired t-tests. Results Although females showed earlier age-of-attainment than males, significant sex differences were only found in stages D-G (p < 0.05). The Demirjian method overestimated the dental age in both males (0.68 ± 1.05 years) and females (0.59 ± 0.97 years). Conclusions The relationship between mineralisation stage and chronological age in this study can be applied as a reference for mandibular dental maturity of Chinese children and adolescents. The Demirjian method overestimated the chronological ages of this sample.